Developing an Effective Community Oral Health Workers—“Promotoras” Model for Early Head Start - Villalta, Jennifer; Askaryar, Hamida; Verzemnieks, Inese; Kinsler, Janni; Kropenske, Vickie; Ramos-Gomez, Francisco (Frontiers in Public Health, 2019)
Purpose: To determine the effectiveness of a train-the-trainer program for Community Oral Health Workers (COHWs) with the goal of reducing Early Childhood Caries (ECC). Methods: 13 Latina caregivers from a local Early Head Start program participated in an 8- hour bilingual oral health training program that provided information & hands-on experiences pertaining to prenatal and children’s oral health. Once trained, the 13 COHWs conducted a series of bilingual interactive oral health promotion workshops at local community sites. Pre/post-tests were conducted after each workshop with a total of 157 caregivers of young children. Bivariate analyses were used to assess changes in knowledge, attitudes and practices of the COHWs and caregivers regarding children’s oral health. Results: Significant positive changes (p <.05) in COHWs’ knowledge were observed for age a child can brush his/her teeth alone and what a pregnant woman with morning sickness can do to protect her teeth. Positive trends were observed for knowing that tap water with fluoride prevents cavities and that poor oral health of parents affects their children’s dental health. While community caregivers in the workshops reported a high consumption of sweet snacks and beverages, there was a significant positive increase (p <.05) in knowledge and attitudes regarding oral health care. Significant increases in knowledge were obtained regarding: when a child can brush his/her teeth well alone, the age when fluoridated toothpaste can be used, ways tooth decay can be prevented, when a child’s first dental visit should be, and what a pregnant woman with morning sickness can do to protect her teeth. Significant positive improvements were found regarding caregiver’s favorable attitude that fluoridated water can help prevent cavities, disagreeing that tap water is dangerous, and agreeing that a parent’s dental health affects their children’s dental health. Conclusions: The study showed a targeted and culturally competent oral health program can significantly improve knowledge, attitudes and self-reported practices of COHWs and the caregivers they trained. Although longitudinal studies are needed to determine if a COHW model can help reduce ECC in underserved communities, preliminary results support the utilization of this model as a viable option that should be expanded.